A functional polymorphism in the pre‐miR‐146a gene is associated with the risk of nonsyndromic orofacial cleft. Issue 5 (15th March 2018) - Pan, Yongchu; Li, Dandan; Lou, Shu; Zhang, Chi; Du, Yifei; Jiang, Hongbing; Zhang, Weibing; Ma, Lan; Wang, Lin
Abstract: microRNAs (miRNAs) are widely involved in craniofacial development, and genetic variants of miRNAs may be associated with the risk of nonsyndromic orofacial cleft (NSOC). Here, we systematically selected five single nucleotide polymorphisms (SNPs) of miRNAs and investigated the associations between these variants and NSOC susceptibility in a two‐stage case–control study including 1, 406 NSOC patients and 1, 578 controls from the Chinese population. We found that compared with the C allele, the rs2910164 G allele of pre‐miR‐146a was associated with an increased risk of NSOC (additive model: odds ratio [OR] = 1.17, 95% confidence interval [CI]: 1.06–1.30, P  = 0.002), including both cleft lip with or without cleft palate (CL/P) and cleft palate only (CPO). Bioinformatic prediction and functional assays revealed that the C allele of rs2910164 was significantly associated with inhibited HEK‐293 and HEPM cell proliferation and decreased abundance of TRAF6. Both miR‐146a and TRAF6 were expressed in the lip tissue samples of NSOC patients, and a moderate inverse correlation was observed between them. Taken together, these results demonstrated that miR‐146a /rs2910164 is associated with susceptibility to NSOC, providing novel insights into the genetic etiology and underlying biology of NSOC. Abstract : miR‐146a /rs2910164 was found to be associated with susceptibility to nonsyndromic orofacial cleft (NSOC) in a two‐stage case‐control study. Bioinformatic prediction and functional assays revealed that the C allele of rs2910164 was significantly associated with inhibited HEK‐293 and HEPM cell proliferation and decreased abundance of TRAF6. Our study provides novel insights into the genetic etiology and underlying biology of NSOC.